Principles of Integrated Marketing Communications : A Malaysia Casebook - Hasrina, Mustafa; Siti Aishah Chu, Abdullah; Shuhaida, Md Noor (Penerbit Universiti Sains Malaysia, 2022)
This book is written primarily as an introductory textbook aimed for both undergraduate and postgraduate students of all institutions of higher learning in the areas of marketing communication, advertising and promotion. It is packed with comprehensive discussion on the essential aspects of integrated marketing communication (IMC) covering on the topics on the conceptualisation, tools, process of implementation, related models and theories, and IMC's measurement of effect. Readers will also learn practical IMC experience through award winning case studies provided by member agencies of the Association of Accredited Advertising Agents Malaysia (4As) and other cutting-edge companies and brands such as Maxis, Malaysia Airports Holdings Berhad, KFC, Langkawi Development Authority, Universiti Sains Malaysia and Wipro Unza.